A Host-Restricted Self-Attenuated Influenza Virus Provides Broad Pan-Influenza A Protection in a Mouse Model - Kim, Minjin; Cheong, Yucheol; Lee, Jinhee; Lim, Jongkwan; Byun, Sanguine; Jang, Yo Han; Seong, Baik Lin (Frontiers in Immunology, 2021)
Influenza virus infections can cause a broad range of symptoms, form mild respiratory problems to severe and fatal complications. While influenza virus poses a global health threat, the frequent antigenic change often significantly compromises the protective efficacy of seasonal vaccines, further increasing the vulnerability to viral infection. Therefore, it is in great need to employ strategies for the development of universal influenza vaccines (UIVs) which can elicit broad protection against diverse influenza viruses. Using a mouse infection model, we examined the breadth of protection of a live influenza vaccine, which was self-attenuated by the host caspase-triggered cleavage of internal viral proteins. A single vaccination in mice induced a broad reactive antibody response against four different influenza viruses, H1 and H5 (HA group 1) and H3 and H7 subtypes (HA group 2). Notably, despite the lack of detectable neutralizing antibodies, the vaccination provided heterosubtypic protection against the lethal challenge with the viruses. Sterile protection was confirmed by the complete absence of viral titers in the lungs and nasal turbinates after the challenge. Antibody-dependent cellular cytotoxicity (ADCC) activities of non-neutralizing antibodies correlated with cross-protection. The cross-protection remained robust even after in vivo depletion of T cells or NK cells, reflecting the strength and breadth of the antibody-dependent effector function. Our data show that the host-restricted designer vaccine serves as a powerful option for developing a UIV, providing pan-influenza A protection against both group 1 and 2 influenza viruses. The promising results of potency, breadth, and safety demonstrated in the mouse model warrant further studies on the development of UIVs.